A Narrative Review on manifestations of gluten free casein free diet in autism and autism spectrum disorders - Akhter, Masnoon; Saara Muddasir Khan; Nadia Firdous; Tikmani, Prashant; Khan, Asra; Rafique, Hamna (Journal of the Pakistan Medical Association, 2022)
Autism and Autism Spectrum Disorder (ASD) are specific neurological disorders that affect the brain, frequently characterised by challenging paediatric behaviour. The current narrative review using PubMed and Google Scholar was conducted in line with the Preferred Reporting Items for Systematic review and Meta-Analysis Protocols, and comprised randomised controlled trials and clinical control trials with gluten-free, casein-free (GFCF) diets published till 2020. Of the 80 studies selected, 7(8.75%) were included in the review. It was observed that the gluten-free, casein-free diet was safe with therapeutic benefits in autistic children. Therefore, a tailored dietary approach can be a beneficial management regimen. The trials related to utility of gluten-free, casein-free diet among autistic children are sparse, with limited sampling size, and indication of bias in the findings. Therefore, larger cohort studies on gluten-free, casein-free trials are required to provide further insight into the therapeutic benefits of the diet.